A New Approach to Improve Quality of Service in SPEED Routing Protocol in Wireless Sensor Network through Data Aggregation - Roustaei, R.; Zohrevandi, E.; Hassani, K.; Movaghar, A. (2009 Second International Conference on Environmental and Computer Science, 2009)
SPEED routing algorithm is a service quality based algorithm in which data aggregation dose not happen. In this article, data aggregation has been added to the conventional technique in SPEED algorithm. The idea involves virtual configuration of sensors and specification of an individual ID to the created data by the sensors in each region, then data aggregation in relay node is done by this ID, resulting in less energy consumption, lower traffic and repeated data, an increase in network lifetime and better quality of service.